2022
DOI: 10.3389/fpls.2022.833747
|View full text |Cite
|
Sign up to set email alerts
|

ARF6s Identification and Function Analysis Provide Insights Into Flower Development of Punica granatum L.

Abstract: Based on the genome and small-RNA sequencing of pomegranate, miRNA167 and three target genes PgARF6 were identified in “Taishanhong” genome. Three PgARF6 genes and their corresponding protein sequences, expression patterns in pomegranate flower development and under exogenous hormones treatments were systematically analyzed in this paper. We found that PgARF6s are nuclear proteins with conserved structures. However, PgARF6s had different protein structures and expression profiles in pomegranate flower developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Both novel 251 and novel 171 targeted gene26063, while miR172 and novel 77 were found to target gene24967. PgmiRNA167 identified three target genes (PgARF6a, PgARF6b, and PgARF6c), and PgARF6a had a directly targeted regulatory relationship with PgmiR167a in pomegranate [29]. According to previous research results, the relationship between pomegranate miRNAs and the target genes will be confirmed in further research.…”
Section: Mirna Target Gene Predictionmentioning
confidence: 54%
See 1 more Smart Citation
“…Both novel 251 and novel 171 targeted gene26063, while miR172 and novel 77 were found to target gene24967. PgmiRNA167 identified three target genes (PgARF6a, PgARF6b, and PgARF6c), and PgARF6a had a directly targeted regulatory relationship with PgmiR167a in pomegranate [29]. According to previous research results, the relationship between pomegranate miRNAs and the target genes will be confirmed in further research.…”
Section: Mirna Target Gene Predictionmentioning
confidence: 54%
“…Our study found that miR167a and miR167d were expressed in the initial stage of ovule development in bisexual flowers and functional male flowers, while the expression of miR167c in the mature stage of the pistils of bisexual flowers was significantly higher than in other developmental stages and in functional male flowers. miRNA target gene prediction showed that PgmiR167a and PgmiR167d have binding sites on the PgARF6s gene sequence [29]. The results showed that PgmiR167s regulated PgARF6s expression to participate in ovule abortion in pomegranate.…”
Section: Discussionmentioning
confidence: 91%
“…To obtain the ovule-related genes expression trends, the transcription levels of genes were obtained from pomegranate bisexual and functional male flowers transcriptome data (PRJNA754480) with vertical diameters of 5.0–10.0 mm (the first stage), 10.1–13.0 mm (the second stage), and 13.1–18.0 mm (the third stage; Zhao et al, 2022 ). RNA-seq and bioinformatics analyses were conducted by Novogene Company (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%